33.1k views
4 votes
–12x + 9 = –15x solve for x

User Newbs
by
4.7k points

2 Answers

4 votes
-12x +9 = -15x
+15x +15x

3x +9 = 0
-9 -9

3x = -9
————
3

x= -3
User Dan Breen
by
6.1k points
5 votes

Answer:

hi there!

the correct answer to question is: x=-3

Explanation:

you move -12x to the other side by adding it on both sides to get: -3x=9 then you divide -3 on both sides to get x=-3

User Schien
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.